Poverty in Colombia /. (A World Bank country study, 1994)
"This report by World Bank economists and Colombian consultants maps out a strategy for poverty reduction in Colombia by concentrating efforts on rural development, social and infrastructural services, and decentralization strengthening. Expenditures would be financed by revenues generated by oil exports, presupposing macroeconomic health and increased government efficiency and accountability"--Handbook of Latin American Studies, v. 57.